MIXED NON-ALBICANS CANDIDA FUNGEMIA: AN UNCOMMON BUT EASILY OVERLOOKED CLINICAL ENTITY - Ding, Chuan Hun; Zaki, Zaili (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The increasing use of invasive medical devices and broad-spectrum antimicrobial agents has resulted in rising candidemia rates throughout the world. A 70-year-old diabetic and schizophrenic woman was admitted initially for staphylococcal sepsis secondary to an infected sacral sore but developed a catheter-related bloodstream infection caused by extended-spectrum Î²-lactamase-producing Klebsiella sp. which necessitated the administration of meropenem. Unfortunately, after a week on the carbapenem, the bacterial sepsis was followed by candidemia. Parenteral fluconazole therapy was started pending identification of the yeast(s). Two distinct Candida species were isolated from her blood which were identified biochemically using ID 32 C as Candida tropicalis and Candida lipolytica. Both yeasts possessed elevated minimal inhibitory concentrations toward fluconazole and although amphotericin B was eventually administered, the patient succumbed to her illness.